PENERAPAN LOCAL BASED CURRICULUM (LBC) PADA PEMBELAJARAN GEOGRAFI UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM BERPIKIR TINGKAT TINGGI DI SMAN 5 PADANG - Zakiah, Meila; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low levels of higher-order thinking skills (HOTS) in Geography at SMAN 5 Padang, particularly in the analysis (C4), evaluation (C5), and creativity (C6) aspects of students, due to learning that is still oriented towards memorization and the lack of utilization of local potential. This study aims to describe the implementation of the Local Based Curriculum (LBC) and analyze its impact on improving students' HOTS. The study used a quantitative approach with a quasi-experimental design and a nonequivalent control group design. The sample size was 72 students, consisting of 36 students in the experimental class and 36 students in the control class. The research instrument was a HOTS test, which has been tested for validity and reliability. Data analysis was conducted using normality, homogeneity, and paired sample t-tests. The results showed that students' HOTS scores in the experimental class were higher than those in the control class. The average score for the experimental class increased from 29.00 to 37.61, a difference of 8.61 points, while the average score for the control class increased from 29.92 to 33.58, a difference of 3.67 points. The results of the hypothesis test showed a significance value <0.001, indicating a significant effect of the implementation of the Local Based Curriculum on the improvement of students' HOTS. Thus, the implementation of the Local Based Curriculum in Geography learning has proven effective in improving students' higher-order thinking skills.